Prognostic value of CD8+ TILs and MMR status and their correlation with clinical outcomes in rectal cancer - Baokun Li; Zesong Meng; Feifei Wang; Chaoxi Zhou; Youqiang Liu; Xuhua Hu; Fei Yang (Discover Oncology, 2026)
Abstract Objective To explore the associations of CD8⁺ tumor-infiltrating lymphocytes (TILs) and mismatch repair (MMR) status with prognosis in patients with rectal cancer. Methods: Formalin-fixed paraffin-embedded (FFPE) tissue specimens were collected from 414 patients with pathologically confirmed stage I–III rectal cancer. Tissue microarrays (TMAs) with a thickness of 4 μm were constructed. Immunohistochemistry (IHC) using anti-CD8 antibody was performed to detect CD8-positive cell expression. MMR status was evaluated via IHC markers including MSH2, MSH6, MLH1 and PMS2. Results CD8⁺ TILs were expressed in T lymphocytes. CD8⁺ TIL density was significantly correlated with tumor invasion depth, lymph node metastasis and MMR status (P0.05). Patients with high CD8⁺ TIL density and proficient MMR (pMMR) exhibited longer overall survival (OS) and progression-free survival (PFS). Univariate and multivariate Cox regression analyses demonstrated that low CD8⁺ TIL density and deficient MMR (dMMR) were independent adverse prognostic risk factors. Conclusion The combination of CD8⁺ TIL density and MMR status may serve as a combined prognostic biomarker for rectal cancer. Higher CD8⁺ TIL density together with pMMR indicates superior patient prognosis, which can provide evidence for developing immunotherapy strategies.